Intraarrest Rhythms and Rhythm Conversion in Asphyxial Cardiac Arrest. (22nd April 2015) - Varvarousi, Giolanda; Chalkias, Athanasios; Stefaniotou, Antonia; Pliatsika, Paraskevi; Varvarousis, Dimitrios; Koutsovasilis, Anastasios; Xanthos, Theodoros; Olson, James E.
Abstract Objectives The objective was to analyze the cardiac arrest rhythms presenting during asphyxial cardiac arrest (ACA). Methods Asphyxial cardiac arrest was induced in 30 Landrace large white piglets, aged 12 to 15 weeks and with a mean (±SD) weight of 20 (±2) kg. After the onset of cardiac arrest, the animals were left untreated for 4 minutes, after which cardiopulmonary resuscitation was commenced. Heart rhythms were monitored from the onset of asphyxia until return of spontaneous circulation or death. Results After endotracheal tube clamping and prior to cardiac arrest, normal sinus rhythm was noted in 14 animals, atrial fibrillation in two animals, Mobitz II atrioventricular block in 10 animals, and third‐degree atrioventricular block in four animals. At the onset of cardiac arrest, seven animals had ventricular fibrillation (VF), two had asystole, and 21 had pulseless electrical activity (PEA). During the 4‐minute period of untreated arrest, however, significant changes in the monitored rhythm were noted; at the end of the fourth minute, 19 animals had VF, two animals had asystole, and nine animals had PEA. Conclusions The most common rhythm after 4 minutes of untreated ACA was VF, while in 57% of animals, PEA was spontaneously converted to VF during the cardiac arrest interval.